Hot Electron Modelling of HEMTs. Issue 1 (2001) - Cole, Eric A. B.; Snowden, Christopher M.; Hussain, Shahzad
Abstract : The hot-electron two-dimensional HEMT with recessed gate is modelled by solving the Poisson, current continuity and energy transport equations consistently with the Schrödinger equation using a finite difference scheme. New expressions are used for the energy densities inside and outside the quantum wells. A method is described for pinning the conduction band at the contact edge to produce an extremely stable numerical solution. Results are presented for an eight layer GaAs-ALGaAs-InGaAs device.